A108 ARE INPATIENTS STILL MORE LIKELY TO FAIL BOWEL PREPARATION IN THE SPLIT-DOSE ERA? FINDINGS FROM 47, 292 COLONOSCOPIES IN THE SOUTHWEST ONTARIO COLONOSCOPY COHORT. (4th March 2021) - Sey, M; Wong, A; McDonald, C; Liu, E Y; Yan, B
Abstract: Background: Prior studies before the widespread use of split-dose bowel preparation have shown a high rate of inadequate bowel preparation in hospitalized patients. Whether this is still true in the era of split-dose bowel preparation is unknown. Aims: To determine the impact of inpatient status on bowel preparation quality in the contemporary era of split-dose bowel preparation. Methods: The Southwest Ontario Colonoscopy cohort consists of all inpatient and outpatient colonoscopies performed between April 2017 and Oct 2018 at 21 hospitals serving a large geographic health region. Procedures done in patients < 18 years of age or by an endoscopist performing <50 colonoscopies/year were excluded. Data were collected through a mandatory quality assurance form that was completed by the endoscopist after each procedure. Pathology reports were manually reviewed. The primary outcome was adequate bowel preparation, defined on an ordinal scale as "good" or "fair" rather than "poor". Secondary outcomes included adenoma detection rate (ADR), sessile serrated polyp detection rate (ssPDR), polyp detection rate (PDR), and cecal intubation rate (CIR). Results: A total of 47, 292 colonoscopies were performed by 75 physicians (36.2% by gastroenterologists, 60% by general surgeons, 4% others), of which 1, 690 were inpatients (3.6%). Inpatients were older (mean 66.8 years vs 60.2 years, p<0.0001), more co-morbid (≥ASA grade 3, 53.6% vs 23.7%, p<0.0001), performed for symptomatic indications (95.7% vs 48.6%, p< 0.0001), have trainee involvement (47% vs 11.6% p<0.001), and less likely to receive split-dose bowel preparation (71.7% vs 91.6% p<0.001). On crude analysis, inpatients were less likely to have adequate bowel preparation (86.2% vs 97.6% p<0.001). On multi-variable analysis, inpatients had lower odds of achieving adequate bowel preparation (OR=0.41, 95% CI 0.33 - 0.50, p<0.001), lower ADR (OR=0.47, 95% CI 0.40 - 0.55, p<0.001), lower PDR (OR=0.54, 95% CI 0.47 - 0.61 p<0.001) and lower CIR (OR = 0.43, 95% CI 0.35 - 0.54, p<0.001). Conclusions: In the era of split-dose bowel preparation, inpatient status is still an important predictor of inadequate bowel preparation with resultant lower quality outcome metrics. Funding Agencies: None